A Review of Intraocular Pressure (IOP) and Axial Myopia - Dongyan Zhang; Liyin Wang; Le Jin; Yingying Wen; Xuhong Zhang; Liyue Zhang; Hong Zhu; Ziyu Wang; Xin Yu; Chen Xie; Jianping Tong; Ye Shen (Journal of Ophthalmology)
The pathogenesis of myopia is driven by genetic and environmental risk factors. Accommodation not only alters the curvature and shape of the lens but also involves contraction of the ciliary and extraocular muscles, which influences intraocular pressure (IOP). Scleral matrix remodeling has been shown to contribute to the biomechanical susceptibility of the sclera to accommodation-induced IOP fluctuations, resulting in reduced scleral thickness, axial length (AL) elongation, and axial myopia. The rise in IOP can increase the burden of scleral stretching and cause axial lengthening. Although the accommodation and IOP hypotheses were proposed long ago, they have not been validated. This review provides a brief and updated overview on studies investigating the potential role of accommodation and IOP in myopia progression.